Effect of Neuroligin1 and Neurexin1 on the Colonic Motility in a Mouse Model of Neuronal Intestinal Dysplasia - Dongming Wang; Ni Gao; Tingting Zhou; Qiangye Zhang; Jian Wang; Aiwu Li (Gastroenterology Research and Practice, 2020)
Aim. To investigate the expressions of neuroligin1 (NL1) and neurexin1 (NX1) in a mouse model of neuronal intestinal dysplasia (Tlx2-/- mice) and to explore their effects on colonic motility. Methods. Immunohistochemistry staining was employed to explore the histological appearances of NL1, NX1, the presynaptic marker of glutamatergic synapses VGLUT1, and the subunit of NMDA receptors of NR1 in the colon of mice with or without Tlx2 mutation. Western blotting and qRT-PCR were performed to detect their relative expressions in the colon. Colonic motility was measured by a glass bead technique. Then, the Tlx2-/- mice were intervened by Huperzine A. Variations on expressions of NL1, NX1, VGLUT1, and NR1 and variations on colonic motility were measured. Additionally, serum concentrations of Glu were measured by ELISA. Results. Immunohistochemistry staining reveals that NL1, NX1, VGLUT1, and NR1 were mainly concentrated in the myenteric plexus of ENS. Compared to those in WT and Tlx2+/- mice, expressions of NL1 and NX1 in colon of Tlx2-/- mice were upregulated with increased VGLUT1 and NR1 abundances and impaired colonic motility (P<0.05). After intervention, the upregulated expressions of NL1 and NX1 were decreased with a correlated reduce of VGLUT1 and NR1 and a recovery of the impaired colonic motility (P<0.05). Variations of serum concentrations of Glu measured by ELISA were in concordance with the variations of glutamatergic synapses and colonic motility (P<0.05). Conclusion. NL1 and NX1 are closely related to the colonic motility through their effects of targeting the formation of glutamatergic synapses and may be involved in the pathogenesis of NID. The variations of serum Glu seem to be a potential and less painful auxiliary measure for colonic motility and NID.